Design and in vitro evaluation of mouth dissolving tablets olanzapine - Sharma, Vivek Kumar; Singh, Vikram; Juyal, Divya; Rawat, Geeta (Journal of Applied Pharmaceutical Research, 2015)
The purpose of this research was to design and evaluate the olanzapine fast dissolving tablets. The variable formulation of Olanzapine having challenging methodology. Olanzapine practically insoluble in water so used different polymers and superdisintigrant to make formulation. Direct compression are most desired method for preparation of mouth dissolving tablets. The tablets were evaluated for disintegration and dissolution properties of the formulation. In formulation of mouth dissolving tablet evaluate the precompression parameter and post compression parameter and after evaluation found satisfactory